An overview of horizontal-axis Magnus wind turbines - Marzuki, Omar Faruqi; Mohd Rafie, Azmin Shakrine; Romli, Fairuz Izzudin; Ahmad, Kamarul Arifin; Abdul Hamid, Mohd Faisal (IOP Publishing, 2018)
Magnus force shows extraordinary results in producing lift force, hence gives rise to its application. One of the applications is by replacing airfoil-shaped blades of wind turbine with the rotating cylinder blades. This is known as Magnus Wind Turbine (MWT), where it generates lift force on the rotating cylinder that perpendicular to the incoming wind flows. Due to high consumption of fossil fuel, natural gas and coal that risk our and earth health. Thus to overcome this conundrum, MWT is one of the innovative approaches to harvest the low wind speed energy. This paper presents an overview of the horizontal-axis MWT state-of-the-art.